Safety on the playground - Raatma, Lucia (Mankato, Minn. : Bridgestone Books, 1999)
Discusses how to safely use swings, slides, and other playground equipment.
Includes bibliographical references (p. 24) and index.
Keywords: Playgrounds -- Safety measures -- Juvenile literature; Playgrounds -- Safety measures; Safety